(3GdeTGcdIs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s ((3HdOI JHQjR s)
(3ChdgG (B:s
(3bO SHb dfG bHd cJGHfG gPG KdGKI YTQ cJGHkG ai GdMjhGf UfYI hEf HYVgG djbhe HHYV s
(3BNQgG (B:s
(3hGdhLg ajg eGjMd hGdYbO eG jTai cd ZQV eGajg ef GdCVYa ajYhO Edi aGageg agPG gh GdeMJGL Edi eYQaJg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B124 - (3U(B126s
(3hQO cPdc ai Qbe (B96s
(3hgh GdebGdI GdQGHYI YTQI ef cJGH GdSHYjfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B105s
Keywords: (3GdcjejGA h GdWHjYjGJs